Analisis Pengaruh Perang Dagang Global Terhadap Kondisi Ekonomi ASEAN 5: Studi Pada Perang Dagang AS-China Periode 2013-2020 - Dikdik Kusdiana; Nurul Hasijah (Universitas Pasundan, 2022)
International trade between countries aims to support economic growth. Indications of the success of international trade carried out by the state can be studied based on the results of the trade balance. In this study, researchers observed the impact of international trade competition activities in ASEAN countries due to the U.S.-China trade war that affects global trade. The study was analyzed through quantitative methods using Random Effect Model (REM) model panel data through the Least Squares Dummy Variable (LSDV) technique. The object of the study observed is the independent variables of the U.S.-China trade balance, balance of payments, imports, and exchange rates. While the dependent variance observed is the economic growth of 5 ASEAN countries (Indonesia, Malaysia, Philippines, Singapore, and Thailand). The results of the analysis of data processing explained that the U.S.-China balance of trade and exchange rates had a significant negative impact on the economic growth of the 5 ASEAN countries. On the other hand, the balance of payments and imports has a positive impact. The model shows that together the variables of the U.S.-China balance of trade, balance of payments, imports and exchange rates have an impact on the economic growth of the 5 ASEAN countries.